Nine‐Step Total Synthesis and Biological Evaluation of Rhizonin A. Issue 11 (1st August 2020) - Liu, Qingchao; Liu, Langlang; Ratnayake, Ranjala; Luesch, Hendrik; Guo, Yian; Ye, Tao
Summary of main observation and conclusion: We have achieved the total synthesis of an architecturally and biologically intriguing cyclic polypeptide, rhizonin A (1 ), in an exceptionally concise and convergent fashion. The strategic route entails 9 longest linear steps to elaborate commercially available materials into the natural product with an overall yield of 9.7%. The brevity of sequence and high overall yield was fueled by the judicious selection of chemical tactics. Rhizonin A (1 ) showed weak inhibitory effects on the cell viability of HCT116 colorectal cancer cells and this activity was dependent on hypoxia‐inducible factors. Abstract :